2015
DOI: 10.3390/buildings5041361
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for Using Building Information Modeling for Energy Analysis of Buildings

Abstract: Building energy modeling (BEM), a subset of building information modeling (BIM), integrates energy analysis into the design, construction, and operation and maintenance of buildings. As there are various existing BEM tools available, there is a need to evaluate the utility of these tools in various phases of the building lifecycle. The goal of this research was to develop guidelines for evaluation and selection of BEM tools to be used in particular building lifecycle phases. The objectives of this research wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(26 citation statements)
references
References 21 publications
0
23
0
Order By: Relevance
“…Typically, the use of BPS to predict energy consumption during building operation requires calibrating the building energy model or the EAM to be as close as possible to how the building will actually be built, occupied and operated (Summerfield & Lowe, 2012;Reeves, Olbina, & Issa, 2015). It was fortunate that the automated BPS workflow experimented in this study allowed users to finely tune the inputs to calibrate the energy model with lots of pre-computed DOE 2.2 whole building energy simulations that represent all worldwide climate zones and a wide range of typical building forms, functions and efficiency (Egger, Autodesk Insight 360, 2015) during the BIM models development and the EAM generations.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, the use of BPS to predict energy consumption during building operation requires calibrating the building energy model or the EAM to be as close as possible to how the building will actually be built, occupied and operated (Summerfield & Lowe, 2012;Reeves, Olbina, & Issa, 2015). It was fortunate that the automated BPS workflow experimented in this study allowed users to finely tune the inputs to calibrate the energy model with lots of pre-computed DOE 2.2 whole building energy simulations that represent all worldwide climate zones and a wide range of typical building forms, functions and efficiency (Egger, Autodesk Insight 360, 2015) during the BIM models development and the EAM generations.…”
Section: Discussionmentioning
confidence: 99%
“…Besides Azhar and Brown (2009), Reeves et al (2012aReeves et al ( , 2015 also evaluated various building energy modeling (BEM) tools to provide guidelines for design and delivery of high-performance buildings. In their research, twelve BEM tools were evaluated by four criteria: interoperability, user-friendliness, available inputs, and available outputs.…”
Section: Bim For Building Performance Analysis (Bpa)mentioning
confidence: 99%
“…(2) Research goal: What BPA types and BIM uses are studied in the collected literature are identified as their central research goals for analyses and discussions. Ten key BPA types are chosen in this study based on the frameworks developed by Azhar and Brown (2009) and Reeves et al (2012Reeves et al ( , 2015. To be noticed, some BPA types are grouped together for they are based on the same physics principles (i.e.…”
Section: Conceptualization Of Topicmentioning
confidence: 99%
See 1 more Smart Citation
“…Gokce et al [26] develop a continuous assessment process by combining the data from different sources and phases in a single data repository centred on a building's BIM spaces. However, Reeven et al [27] highlight that a limitation in using BIM (associated with the building energy model (BEM)) for monitoring the building performance in operation is its "inability to simulate building performance under realistic conditions". Indeed, these authors mention that "inaccurate input related to occupant behavior and building operation is a common and substantial source of error in building performance simulations under realistic conditions".…”
Section: Related Work and Backgroundmentioning
confidence: 99%